Role of high resolution sonography and color Doppler flow imaging in the evaluation of scrotal pathology - Gupta, Ashish Kumar; S., Shrinuvasan; Shetty, Srikanth Sanjeev; R., Chidambaram (International Journal of Research in Medical Sciences, 2017)
Background: Scrotal swelling and pain are frequently encountered in clinical practice. Although to reach a diagnosis in some patients, history and physical examination are adequate, yet in a large percentage of patients, some additional studies are essential for complete evaluation of their symptoms. The clinical examination is often misleading or non-specific. The study shows the application of Gray-scale sonography, Color Doppler flow imaging (CDFI) and Power Doppler (PD) in the diagnosis of swelling, malposition, torsion, trauma, varicocele, hydrocele, cyst, mass, and atrophy. Methods: A total of 93 patients from all age groups with symptoms related to scrotal disease have been included in this study. Gray-scale sonography, CDFI and PD sonography of scrotal lesions were carried out. Results: A good correlation was seen in the comparison of scrotal lesions between sonography (gray scale, CDFI, and PD) and histopathology/ treatment response. Conclusions: High-resolution sonography, along with color Doppler flow imaging and power Doppler should be used as the first-line investigation in the evaluation of scrotal pathologies. Color Doppler flow Imaging and power Doppler add useful information and complement gray-scale sonography in reaching a correct diagnosis.